2008
DOI: 10.1242/jeb.014613
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen profiles in egg masses predicted from a diffusion–reaction model

Abstract: SUMMARYWe developed a novel diffusion-reaction model to describe spatial and temporal changes in oxygen concentrations in gelatinous egg masses containing live, respiring embryos. We used the model in two ways. First, we constructed artificial egg masses of known metabolic density using embryos of the Antarctic sea urchin Sterechnius neumayeri, measured radial oxygen profiles at two temperatures, and compared our measurements to simulated radial oxygen profiles generated by the model. We parameterized the mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 17 publications
1
21
0
Order By: Relevance
“…For molecules in biological structures, such as egg mass gel, the temperature sensitivity of diffusive transport also depends on temperature sensitivity of structural properties. For egg masses of both temperate and Antarctic Tritonia, we directly measured temperature effects on O 2 diffusion coefficients (Woods and Moran, 2008), finding negligible increases across the same temperature ranges that stimulated large increases in metabolic rates, thus confirming the assumption of temperature-insensitivity of O 2 transport. Here we measure all remaining model parameters -embryo metabolic rates, diffusion coefficients of O 2 and radial profiles of O 2 -at both ambient water temperature of McMurdo Sound (-1.8°C) and slightly warmer temperatures (+1.5-2°C) in egg masses of the Antarctic dendronotid nudibranch Tritonia challengeriana Bergh 1884.…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…For molecules in biological structures, such as egg mass gel, the temperature sensitivity of diffusive transport also depends on temperature sensitivity of structural properties. For egg masses of both temperate and Antarctic Tritonia, we directly measured temperature effects on O 2 diffusion coefficients (Woods and Moran, 2008), finding negligible increases across the same temperature ranges that stimulated large increases in metabolic rates, thus confirming the assumption of temperature-insensitivity of O 2 transport. Here we measure all remaining model parameters -embryo metabolic rates, diffusion coefficients of O 2 and radial profiles of O 2 -at both ambient water temperature of McMurdo Sound (-1.8°C) and slightly warmer temperatures (+1.5-2°C) in egg masses of the Antarctic dendronotid nudibranch Tritonia challengeriana Bergh 1884.…”
Section: Introductionsupporting
confidence: 56%
“…Likewise, Bosch et al (Bosch et al, 1987) and Stanwell-Smith and Peck (Stanwell-Smith and Peck, 1998) found that the effect of temperature on developmental rate in polar echinoderms was much stronger than for temperate or tropical species: Q 10 values of 10-15 between -2°C to +2°C, far outside the normal biological range (2-3). A counterexample is provided by the data reported in the previous paper (Woods and Moran, 2008) on another polar echinoderm, Sterechinus neumayeri, which showed that it had a low Q 10 (~1.5).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Oxygen-and capacity-limited thermal tolerance (or, in other words, temperature-dependent oxygen limitation) has also been verified in larval stages of for example crustaceans ) as well as in small zooplankton (Seidl et al, 2005). All of these observations match with a more general picture of how ambient oxygen levels shape and limit animal life through oxygen availability, be it in the limited capacity of adult specimens to ventilate their oxygen-limited egg masses (Cohen and Strathmann, 1996;Woods and Moran, 2008;Fernandez et al, 2000) or in the dependence of maximum body size of marine invertebrate phyla on temperature-dependent oxygen solubility and thus aquatic oxygen levels (Chapelle and Peck, 1999). These principles thus appear unifying in shaping (aquatic and possibly terrestrial) animal life, firstly referring to individual species.…”
Section: Introductionmentioning
confidence: 62%
“…Further limitation (in invertebrates) may involve the ventilatory system. In special cases, such as in adult crustaceans, ventilation of the egg masses is also limited by capacity (Cohen & Strathmann 1996, Fernandez et al 2000, Woods & Moran 2008. The balance between oxygen supply and demand shapes the dependence of maximum body size in marine invertebrate phyla on temperature-dependent oxygen availability (Chapelle & Peck 1999, Pörtner 2002b.…”
Section: Introductionmentioning
confidence: 99%